Ecologic Service, Economic Benefits, and Sustainability of the Man-Made Ecosystem in the Taklamakan Desert - Congjuan, Li; Abulimiti, Madinai; Jinglong, Fan; Haifeng, Wang (Frontiers in Environmental Science, 2022)
The longest artificial highway shelterbelt flow across the Taklimakan desert has been conducted in 2005. To ensure the sustainable development of the highway and shelterbelts, scholars have carried out a large number of studies on the shelterbelt since 1991. This review is based on a no ongoing 30-year monitoring program from 1991-2021. We find that with the increase of shelterbelt age, some ecological and economic benefits gradually appear. Such as saving transportation cost, promoting economic development in Southern Xinjiang, Improving the sandy soil and microenvironment, and increasing the biodiversity. At the same time, some adverse phenomena also exist, such as the high maintenance costs, water tables decreasing because of irrigation, threats of the protected species, pollution from pumping oil wells, and the potential damage from highway burying as sand dunes move forward. In view of these problems, some suggestions are as follow. Firstly, the science-policy sections of both the UNFCCC the UNCCD should pay special attention to provide research-based guidance for the international cooperation and coordination. Secondly, China government should provide the necessary funding to establish the 27th China desert observation and research station to ensure long-term monitoring, and slow the pace of construction on the desert highway to allow time to develop strategies that minimize the impact on wild animals. Thirdly, it is necessary to apply solar photovoltaic power in well irrigation and sand industry development. Fourthly, the sand-blocking belt of 10 m in width and 10 m away from the outside of upwind shelterbelt can be laid every five years in view of sand-buried roads. In short, the inter-agency collaboration and coordination are both essential to ensuring the success of sustainable development and management of the Taklimakan Desert Man-made Ecosystem.